2002
DOI: 10.1021/la0258953
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of Alkanethiol-Terminated Poly(ethylene glycol) on Gold

Abstract: The grafting of alkanethiol-terminated poly(ethylene glycol) [HS(CH2)11(OCH2CH2)n-OCH3; n ) 34-56, MW ≈ 2224 Da] onto polycrystalline gold from dilute solutions was investigated by ellipsometry, X-ray photoelectron spectroscopy, infrared reflection-absorption spectroscopy, and in situ second harmonic generation. After immersion of a gold-coated Si wafer into a 50 µM dimethylformamide solution, the thickness of the grafted layer increases in a first rapid step up to ∼20 Å. After about 10 min, the thickness rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
108
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(128 citation statements)
references
References 52 publications
19
108
1
Order By: Relevance
“…There have been some reports on grafting 2 kDa PEG thiol chains. For example Unsworth et al 8 reported a maximum graft density of 0.58 chains/nm 2 using methoxy capped 2 kDa PEG thiol chains under cloud point conditions, and Tokumitsu et al 34 reported a maximum graft density of 3.6 chains/nm 2 using 2 kDa PEG conjugated to undecane thiols. Theoretical maximum graft density that can be obtained using PEG SAM is 4.8 chains/nm 2 , assuming the molecular cross-sectional area for PEG brush in helical conformation to be 22 Å 2 as reported by Harder et al 22 From XPS data we have calculated a graft density of PEG-COOH SAM to be 1.0 chain/nm 2 using Eqs.…”
Section: E Discussionmentioning
confidence: 99%
“…There have been some reports on grafting 2 kDa PEG thiol chains. For example Unsworth et al 8 reported a maximum graft density of 0.58 chains/nm 2 using methoxy capped 2 kDa PEG thiol chains under cloud point conditions, and Tokumitsu et al 34 reported a maximum graft density of 3.6 chains/nm 2 using 2 kDa PEG conjugated to undecane thiols. Theoretical maximum graft density that can be obtained using PEG SAM is 4.8 chains/nm 2 , assuming the molecular cross-sectional area for PEG brush in helical conformation to be 22 Å 2 as reported by Harder et al 22 From XPS data we have calculated a graft density of PEG-COOH SAM to be 1.0 chain/nm 2 using Eqs.…”
Section: E Discussionmentioning
confidence: 99%
“…Conversely, too many tethers may cause the resulting elevated membrane to be sparingly fluid and the compact structure of the elevated membrane may impede spanning of proteins through the bilayer. Therefore, a sparsely tethered bilayer resting over a protein resistant biocompatible support such as polyethylene glycol 28,29 ͑PEG͒ may provide a yet incremental advancement on previous work on elevated membranes. This type of architecture would also provide a truly biomimetic cell membrane model.…”
Section: Introductionmentioning
confidence: 99%
“…50,51 The adsorption kinetics for these PEG-like thiol compounds deviated remarkably from a Langmuir model, and displayed an extended period ͑ϳ10 min͒ within which hardly no adsorption appears to take place. Contrary, the formation of the EG 6 C 16 SAM is reminiscent of Langmuir kinetics, which also was found to satisfactory describe the formation of "simple" alkylthiolate SAM studied under similar experimental conditions.…”
Section: Discussionmentioning
confidence: 98%